Violence, bullying and academic performance in higher education students - Ramos rodríguez, Irma (Advances in Social Sciences Research Journal, 2021)
Violence and bullying affect the physical, mental, social and academic well-being of students. The objective of this work was to analyze the association between violence and bullying, with academic performance in higher education students, a descriptive, cross-sectional, analytical study was carried out in first semester students of different higher level careers, the information was obtained with the application of two questionnaires, the first about Socio-demographic Data and the second one was the questionnaire of School Violence from the Ombudsman (2000). In the results, it was found that 37.4% of the participants showed a grade point average ≥90 points, 47% between 75 to 89 points and 15.6% an average <75 points. Poor academic performance was significantly associated with the type of career, with being ignored, being threatened to scare him, with suffering violence due to social exclusion, harassment in general, harassment due to social, physical and sexual exclusion. In conclusion, violence and bullying are two serious problems that university students frequently face, the effects produced by them affect the physical and mental health of the victims and can affect their academic performance.